2014
DOI: 10.1007/s00213-014-3519-0
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline, low dose naltrexone, and their combination for heavy-drinking smokers: human laboratory findings

Abstract: Rationale Heavy drinking smokers constitute a sizeable and hard-to-treat subgroup of smokers, for whom tailored smoking cessation therapies are not yet available. Objectives The present study used a double-blind, randomized, 2×2 medication design, testing varenicline alone (VAR; 1mg twice daily), low dose naltrexone alone (L-NTX; 25mg once daily), varenicline plus naltrexone, and placebo for effects on cigarette craving and subjective response to alcohol and cigarettes in a sample (n=130) of heavy drinking d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 79 publications
1
48
1
Order By: Relevance
“…They also noted that participants with less than a high school education smoked at the highest rate, and that the benefit of combined therapies for this subgroup might reflect greater nicotine dependence. There is also evidence that combined pharmacotherapy could improve cessation outcomes for people with a predefined illness (including cardiovascular disease, cancer, diabetes, and chronic obstructive pulmonary disease) (Steinberg et al, 2009) and with co-occurring heavy alcohol use (Ray et al, 2014).…”
Section: Respecting Individual Differences and Preferences In Cessatimentioning
confidence: 99%
“…They also noted that participants with less than a high school education smoked at the highest rate, and that the benefit of combined therapies for this subgroup might reflect greater nicotine dependence. There is also evidence that combined pharmacotherapy could improve cessation outcomes for people with a predefined illness (including cardiovascular disease, cancer, diabetes, and chronic obstructive pulmonary disease) (Steinberg et al, 2009) and with co-occurring heavy alcohol use (Ray et al, 2014).…”
Section: Respecting Individual Differences and Preferences In Cessatimentioning
confidence: 99%
“…Recent clinical trials have shown promising results in subjects treated with varenicline, an FDA-approved aid for smoking cessation. Alcohol-dependent individuals who received varenicline treatment reported a significant decrease in alcohol cravings and consumption when compared with placebo-treated controls (Erwin and Slaton, 2014;Litten et al, 2013;Ray et al, 2014). The exact mechanism underlying the ability of varenicline treatment to reduce alcohol consumption is not well understood as changes in alcohol consumption because of varenicline are independent of patients smoking status (Litten et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, upon cessation of both nicotine and ethanol, acetylcholine levels increase and dopamine levels decrease in the NAc. In addition, varenicline, a partial nicotinic acetylcholine receptor (nAChR) agonist used for nicotine cessation therapy, may reduce alcohol consumption in heavy smokers (Erwin and Slaton, 2014;Litten et al, 2013;Ray et al, 2014), further underscoring the role of nAChRs in the mechanisms of alcohol addiction (Chatterjee and Bartlett, 2010;Rahman et al, 2014). Moreover, brain areas that have been shown to regulate affective behavior and nicotine withdrawal symptoms are possible candidate regions for regulating the emergence of withdrawal-associated behaviors after ethanol cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings on safety and mechanisms are vital to deciding whether to invest resources for efficacy testing for a putative addiction medication. Our team has used human laboratory paradigms to test several medications for addiction, including naltrexone (Ray, Bujarski, Chin, & Miotto, 2012;Ray & Hutchison, 2007), topiramate (Miranda et al, 2008;Ray et al, 2009), quetiapine (Moallem & Ray, 2012;Ray, Chin, Heydari, & Miotto, 2011), and varenicline (Ray et al, 2014(Ray et al, , 2013. Given the new opportunities presented by recent discoveries on the role of neuroinflammation in addiction as well as new advancements in the technology of medication development, including the refinement of powerful human laboratory models, the stage is set for the discovery of novel treatments for substance use disorders.…”
Section: Discussionmentioning
confidence: 99%